(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: So far few studies were done to determine predictors of neonatal mortality in Ethiopia. This study was aimed to provide information on the incidence and risk factors of neonatal survival in Eastern Ethiopia from September, 2007 to August, 2012. Methods: The study uses data extracted from Kersa Health and Demographic Surveillance (Kersa HDSS) System database, which is located in the Oromiya Regional State, Eastern Ethiopia. The surveillance system is an open cohort, which was established in 2007. Data extraction includes all live births recorded in the system. The main outcome variable was the occurrence of death within 28 days after birth (neonatal death). The survival time was calculated in days using the time interval between the date of birth and date of event (death). Kaplan-Meier model and Cox-proportional hazard techniques were used to identify predictors of neonatal death. Results: The overall, Early and Late Neonatal Mortality Rate was 28.37, 19.55 and 8.82 per 1000 live births, respectively. A Neonatal Mortality Incidence Rate was 1 per 1000 (95% CI, 0.87-1.15) person days. Risk factors of neonatal survival include birth type (HR=5.40; 95% CI, 3.64-8.02), preterm birth (HR=11.17; 95% CI, 7.17-17.40), and previous infant sibling born (died HR=2.15; 95% CI, 1.39-3.33: no previous birth HR=1.78; 95% CI, 1.17-2.72). Conclusion: A significantly high level of neonatal mortality incidence rate was observed, which majority of the neonatal deaths were found to occur at early neonatal period. Therefore, efforts needs to be exerted in addressing the risk factors identified as predictors of neonatal mortality.